Evaluation of a radioimmunoassay for histamine measurement in biologic fluids - McBride, Paul; Bradley, Diane; Kaliner, Michael (Journal of allergy and clinical immunology, 1988)
A new radioimmunoassay for the measurement of histamine in biologic fluids was evaluated. Assay selectivity and specificity were achieved by “succinyl-glycinamide derivatization” of histamine in samples to mimic the immunogen used to generate the monoclonal antibody. The assay exhibits a linear response from 0.1 to 5.0 ng/ml of histamine and the monoclonal antibody used has partial recognition of only N-methylhistamine (other than histamine). With minimal modifications, the assay can accurately measure histamine in plasma, urine, and buffer. Normal ranges for human subjects were established: plasma levels are 0.193 ± 0.08 ng/ml (n = 40) and urine levels are 20.9 ± 11.2 μg histamine/gm creatinine (n = 10).